Sociocultural heritage of Alaska’s Russian-speaking population: traditions, customs, way of life - Dmitry V Shevtsov; Ana Teresa Gutiérrez del Cid (RUDN Journal of Russian History, 2018)
The article considers the problem of the cultural heritage of the Russian colonization of the north-eastern part of the Pacific region.The authors examine the influence of the Russian culture on the life of the indigenous population of Russian America after its sale in 1867. The study demonstrates the borrowings of the traditional elements of everyday life, the customs of the native population, the Russian legacy in the place-names and languages of the indigenous peoples of Alaska, and other problems. One of the key issues of the study is the preservation and prevalence of the Russian language, as well as of the Russian-language periodicals in the region.The article contains newspapers data, eyewitnesses’ recollections, materials of authoritative investigations on this issue, etc. The authors come to conclusions that after 1867 the Russian language remained widespread only in the Russian-Creole population centres: Sitka, Kodiak, Kenai Peninsula. In the rest of Alaska,the language was quickly ousted and replaced with English. The indigenous population adopted several elements of everyday life from the colonists, mostly furniture, tools, clothes. By the early 20thcentury, the most part of these things had been replaced by more modern American objects. After 1867 the Russian Orthodox Church remained one of the few forces to be able to preserve the Russian culture in the region. In the 1870s and 1890s, there were extensively opened new parishes and Russian-language schools. However, in the early 20th century the influence of the Russian Orthodox Church considerably decreased due to the policy of accelerated Americanization and the emergence of Catholic and Protestant missions in Alaska.